PENGARUH BRAND IMAGE TERHADAP LOYALITAS PELANGGAN DI TOKO OLEH-OLEH MALANG STRUDEL - Palevi, Reza; Leli Kusuma Dewi, Luh Gede; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 1 (2018): Jurnal IPTA (July 2018)DO - 10.24843/IPTA.2018.v06.i01.p07, 2018)
This study aims to determine the effect of brand image to customer loyalty in Malang Strudel Souvenir Store. The rapid development of Malang Strudel is the foundation of this research. In this study, the customer is tourist who visiting Malang and shopping for souvenirs at Malang Strudel Souvenir Store. This research uses quantitative descriptive data analysis technique using SPSS ver. 20 for Windows. Data were collected by distributing questionnaires to 166 respondents.This research is quantitative research using reliability test method, validity test, classic assumption test, correlation analysis, coefficient determination test, multiple linear regression analysis, t test, and f test. The variables used in this research are the strength of brand association (X1), uniqueness of brand association (X2), brand association advantage (X3) as independent variable and Customer Loyalty (Y) as dependent variable.The result of this research is strength of brand association (X1) and favorability of brand association (X3) have positive and significant influence, while uniqueness of brand association (X2) has positive and insignificant effect. Simultaneously, strength of brand association (X1), uniqueness of brand association (X2), and favorability of brand association (X3) that make up the brand image, have an impact on customer loyalty. A total of 54.1% of customer loyalty can be explained by variable strength, uniqueness, and favorability. While the rest of 45.9% customer loyalty can be explained by other variables that have not been studied in this research.